2023
DOI: 10.3390/agronomy13092231
|View full text |Cite
|
Sign up to set email alerts
|

Design and Testing of Bionic-Feature-Based 3D-Printed Flexible End-Effectors for Picking Horn Peppers

Lexing Deng,
Tianyu Liu,
Ping Jiang
et al.

Abstract: To solve the problems of poor adaptability and large sizes of pepper harvesting machinery in facility agriculture to enhance the efficiency and quality of pepper harvesting and ultimately boost farmers’ income, several flexible end-effectors were designed. These end-effectors were tailored to the unique morphologies of horn peppers, drawing inspiration from biomimicry. Subsequently, we conducted experimental verification to validate their performance. Four biological features, namely, the outer contours of a V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Picking methods based on intelligent algorithms have high picking accuracies. Deng et al designed a flexible and effective method for chili picking [5]. The drum snap finger picking device has the advantages of picking flexibility and high variety adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…Picking methods based on intelligent algorithms have high picking accuracies. Deng et al designed a flexible and effective method for chili picking [5]. The drum snap finger picking device has the advantages of picking flexibility and high variety adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that our improvements were very effective in enhancing the detection performance of the proposed model. In addition, our improved algorithm is well suited for edge deployment and embedded development with the help of some control algorithms [43] and hardware device [44], as the inference speed of the model ensures the feasibility of real-time detection. 3.…”
mentioning
confidence: 99%